New paromomyids (Mammalia, Primates) from the Paleocene of southwestern Alberta, Canada, and an analysis of paromomyid interrelationships. (March 2023) - Scott, Craig S.; López-Torres, Sergi; Silcox, Mary T.; Fox, Richard C.
Abstract: Paromomyidae are one of several families of plesiadapiforms that flourished during the Paleocene in North America soon after the extinction of non-avian dinosaurs some 66 million years ago. Although they are often among the best-represented plesiadapiforms in mammalian faunas in both North America and Europe, the early history of paromomyids is poorly understood, and their fossil record at higher latitudes is comparatively depauperate. We report here on the discovery of two new species of paromomyids from Paleocene deposits in southwestern Alberta: Edworthia greggi new species is the second known species of the basal paromomyid Edworthia Fox, Scott, and Rankin, 2010 whereas Ignacius glenbowensis new species is among the most abundantly represented species of Ignacius Matthew and Granger, 1921 . These new discoveries document, for the first time, parts of the upper dentition of Edworthia, and the new species of Ignacius represents the first new, pre-Clarkforkian species of the genus to be described in nearly 100 years. A comprehensive phylogenetic analysis of nearly all known paromomyid taxa (including the new species described herein) recovered both species of Edworthia near the base of the paromomyid tree in a polytomy with Paromomys depressidens Gidley, 1923 and a paraphyletic Ignacius . The new paromomyids from Alberta not only increase the known taxonomic diversity of Edworthia and Ignacius but also add significantly to knowledge of the dental anatomy of these poorly known genera and further add to a uniquely Canadian complement of Paleocene plesiadapiforms. UUID: http://zoobank.org/a2f31cfe-09b9-4168-b09f-9d0c3d0af342